Sekundarna sukcesija v kisloljubnih gozdovih rdečega bora na Golovcu (Slovenija) v obdobju 1942–2024 - Čulajević, Luka (Acta silvae et ligni, 2026)
The study examines changes in acidophilous Scots pine forests on Golovec Hill between 1942 and 2024, based on repeated phytosociological surveys conducted by Prof. Gabrijel Tomažič and additional contemporary relevés. The results show a marked decline in species diversity, particularly in the herb and shrub layers, as well as a retreat of Scots pine, which is being replaced by beech, sessile oak, sweet chestnut, and Norway spruce. Moss cover has decreased sharply, while bracken and bilberry have become even more dominant. Phytoindication reveals reduced light availability in stands, increased nutrient levels, and lower soil acidity as a result of the abandonment of litter raking and the accumulation of deciduous leaf litter. The analysis indicates that secondary succession is progressing from former pioneer pine stands through more or less long-lasting stages of mixed oak–chestnut forests toward acidophilous beech forests, which have already established themselves on more favourable sites. Golovec is now characterized primarily by transitional and variably advanced successional stages of mixed forests.
Keywords: acidophilous forests; beech; bukev; Castanea sativa; Fagus sylvatica; fitocenologija; Golovec; kisloljubni gozdovi; kostanj; phytosociology; Pinus sylvestris; rdeči bor; Scots pine; secondary succession; sekundarna sukcesija; species diversity; sweet chestnut; vrstna pestrost